Experimental investigation on structural behavior of micro and macro fibre reinforced concrete beams subjected to cyclic loading - Kalaivani, M.; Vennila, G. (Journal of Structural Engineering, 2024)
The structural performance of concrete made with commercially available steel fibres has been investigated. Two types of steel fibres, short crimped of length 15mm and aspect ratio of 37.5, another of long hooked ends of length 30 mm and aspect ratio of 60 were used in the present study. The overall volume fraction of steel fibres were restricted to 1 percent by the volume of concrete. M30 grade of concrete was used to cast the specimens. Reinforced concrete beams of 1.5 m length and 100x150mm in cross section were cast with different percentages of micro and macro steel fibres and the specimens were tested under two point forward cyclic loading after 28 days of curing. The various parameters such as stiffness, ductility and energy absorption capacity or toughness were evaluated and compared with the conventional RC beam. The short crimped fibre delays the initial crack when compared to all the specimens. The combination of micro and macro steel fibre increases the stiffness, ductility and energy absorption capacity significantly. The optimum fibre proportion of long hooked and short crimped for hybrid fibre reinforced concrete beam was found to be 0.8:0.2 for overall better performance as compared to that of the conventional beam..